A Novel Role for the Periaqueductal Gray in Consummatory Behavior - Tryon, Valerie Lee; Mizumori, Sheri J. Y. (Frontiers in Behavioral Neuroscience, 2018)
The periaqueductal gray (PAG) has a well-established role in pain processing, autonomic function, and behavioral responses to fear. Anatomical work suggests the PAG may mediate food intake and reward processing as it has extensive reciprocal connections within brain circuits that mediate appetitive processes and consummatory behaviors such as prefrontal cortex, hypothalamus, amygdala, parabrachial nucleus, and ventral tegmental area (Kelley et al., 2005). Therefore, we investigated if the PAG of hungry rats has a functional role in appetitive and consummatory behaviors. To address this, PAG was pharmacologically inactivated during a spatial working memory task with muscimol (0.1-0.3µg), a GABAA agonist vie intracranial infusion. Inactivation of PAG led to reduced intake of food rewards and increased errors on this task. To focus on the specific effects PAG inactivation had on food consumption, PAG was inactivated during two separate food intake tasks in a separate group of rats. Again, PAG inactivation resulted in a significant decrease in food consumption, as well as an increased latency to consume food. We next investigated PAG neural responses to reward encounters. A different group of rats performed the same task used in Experiment 1 while the in-vivo activity of PAG neurons was recorded. In a subset of PAG neurons, reward encounters elicited phasic excitation. A separate subset of PAG neurons were inhibited during reward encounters. These responses scaled with the size of the reward, with sustained excitation or inhibition in response to large rewards compared to small. Our data also show that separate groups of PAG neurons in awake behaving animals display either increased and decreased neural responses to reward encounters. Additionally, a proportion of neurons were modulated by the animals’ velocity. This study is the first to show that PAG neurons process reward-related information, perhaps to mediate consummatory behaviors related to food consumption.